WordPress Web design for dummies - Sabin-Wilson, Lisa (--For dummies., 2016)
Provides information on using WordPress to create and maintain a Web site, covering such topics as text editors, choosing colors and fonts, themes and templates, widgets, CSS, HTML, CMS, and plugins.